2007
DOI: 10.1111/j.1442-9071.2006.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane transplantation for ocular surface reconstruction: indications and outcomes

Abstract: Use of AMT can be associated with a significant number of failures. It provides a useful alternative for specific indications where its use should be encouraged. It is important to define criteria for success in order to accurately evaluate efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 38 publications
0
58
0
Order By: Relevance
“…As mentioned above, the prognosis is worse for progressive cicatrising conjunctival disease (with associated chronic inflammation) than for stable, non-progressive cicatrisation. 27 Glaucoma Similar to its use in symblepharon treatment, AM has been used as an adjunct in glaucoma surgery and as a treatment option in its complications. Its main purpose has been to reduce scarring at the time of filtering surgery, to repair early or late leaks, and act as a cover for valve procedures.…”
Section: Symblepharonmentioning
confidence: 99%
“…As mentioned above, the prognosis is worse for progressive cicatrising conjunctival disease (with associated chronic inflammation) than for stable, non-progressive cicatrisation. 27 Glaucoma Similar to its use in symblepharon treatment, AM has been used as an adjunct in glaucoma surgery and as a treatment option in its complications. Its main purpose has been to reduce scarring at the time of filtering surgery, to repair early or late leaks, and act as a cover for valve procedures.…”
Section: Symblepharonmentioning
confidence: 99%
“…The hAM is an abundant birthing tissue that, due to its unique structure, composition, and neonatal derivation, has had promising results when used in a number of tissue repair applications. [11][12][13][14][15][16][17]33 Based on these clinical successes and a novel approach that takes advantage of the hAM's unique properties, we have developed a concentric rolling approach that aims at rapidly forming cell-dense and mechanically stable tissue-engineered blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] However, all these applications have used the hAM as an acellular material, without taking advantage of the material's capacity to be seeded or used as a layered construct to speed and potentially enhance tissue regeneration. The hAM presents a number of desirable characteristics (advantageous for blood vessel regeneration and a wide range of tissue-engineering applications), including biocompatibility, biostability, noninflammatory, nontoxic, noncarcinogenic, nonimmunogenic, 17 vasoactivity, thromboresistance, 18 ability to remodel, 16 infection resistance, suture-holding capacity, 19 and its wide availability.…”
mentioning
confidence: 99%
“…Without the limbal stem cells and corneal epithelial cells, the cornea may not maintain avascularity and clarity because of secondary conjunctivalization and neovascularization of the cornea. In a retrospective case study, Maharajan et al (2007) reported the correlation between a higher success rate of ocular surface reconstruction using amniotic membrane transplantation and the availability of stem cells. There are some minor disadvantages of amniotic membrane transplantation.…”
Section: Disadvantages Of Human Amniotic Membranementioning
confidence: 99%